1970
DOI: 10.5424/sjar/20110901-075-10
|View full text |Cite
|
Sign up to set email alerts
|

Germination and emergence variability of alfalfa (Medicago sativa L.) landraces collected in Southern Tunisia oases

Abstract: Alfalfa (Medicago sativa L.) is one of the most important forage crops in the world. It has been originated from the Caucasus region (Michaud et al., 1988). The species presents purple flowers, a tap root, an erect growth habit, coiled pods and no winter dormancy. This plant improves the yield and quality of the following crops by atmospheric nitrogen fixation (Bruulsema and Christie, 1987 AbstractVariability in germination under controlled conditions with and without salt, seeds characteristics and field eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Parallel to our findings, significant variations were observed with respect to morphological, phenological, biological and molecular properties between populations in previous studies (Maureira et al 2004;Jafari & Goodarzi 2007;Tucak et al 2009;Benabderrahim et al 2009Benabderrahim et al , 2011Xavier et al 2011). The reason for this variation detected within populations may be related to genetic structure, which is probably due to heterozygosis of cross-pollination of alfalfa (Prosperi et al 2006).…”
Section: Discussionsupporting
confidence: 78%
“…Parallel to our findings, significant variations were observed with respect to morphological, phenological, biological and molecular properties between populations in previous studies (Maureira et al 2004;Jafari & Goodarzi 2007;Tucak et al 2009;Benabderrahim et al 2009Benabderrahim et al , 2011Xavier et al 2011). The reason for this variation detected within populations may be related to genetic structure, which is probably due to heterozygosis of cross-pollination of alfalfa (Prosperi et al 2006).…”
Section: Discussionsupporting
confidence: 78%
“…Seed germination is extensively reported to be reduced, retarded [4] , [57] , [58] or completely inhibited [59] at high salinities. Similarly, seeds of Excoecaria agallocha showed clear preference for low salinities from 0 to 5 psu, and salinity beyond 15 psu significantly delayed root initiation and seedling establishment.…”
Section: Discussionmentioning
confidence: 99%
“…Benabderrahim et al (2011) also reported significant differences in seed emergence among 20 lucerne landraces from Tunisia. Nevertheless, the effect of variety could not be separated from the effect of seed lot in our experiment.…”
mentioning
confidence: 82%
“…Benabderrahim et al (2011) demonstrated a significant effect of lucerne landrace and geographic origin on germination and field emergence. All Czech lucerne varieties have three national landraces (Hodonínka, Přerovská, Kaštická) in their pedigree, which were naturally differently influenced by sickle lucerne (Medicago falcata L.) considered as a genetic source for im-proving the adaptability of lucerne due to a higher tolerance to low pH (Jelinowska 1964).…”
mentioning
confidence: 95%